Central Asian integration as a way of guaranteeing regional security, economic growth: feasibility and prospects - Najmitdinov, Ahadhon; Justus Liebig University Giessen (My University, 2010)
Nowadays, CA countries are facing serious challenges. Their industries are slowly recovering from the disruption of supplier-producer ties among former Soviet republics and East European states. The transformation from centrally-planned economies into market oriented ones requires absolute reconsideration of political and economic values. The focus towards industrialization has been implemented. For instance, Uzbekistan is among the very few former USSR countries which have developed motor-car and aircraft industries. The textile industry is another sector which is currently experiencing a boom. Expansion of Turkish and South Korean businesses and inflow of substantial investments from these countries can be observed currently in several CA states. Financial inflows from these countries are directed towards motor-car and textile industries as well as hotel and tourist infrastructure. CA is a potentially good area for foreign investors. Besides the industrial sector, the financial sphere is another field where fruitful collaboration with foreign countries could take place. The financial system in most CA states is still restructuring and developing. Significant human resources and comparatively much lower wage rates and costs of production make CA attractive for investing. In order to attract foreign investments, a number of preconditions have to be met: - Political stability and security must be achieved; - Trade barriers should be removed; - Transportation infrastructure within the region needs to be improved. Achieving these points implies integration! Integrated CA is more likely to be able to cope with challenges of today s insecure world. Moreover, integrated CA has better chances to assert its claims and interests, especially, CSR resources distribution, balancing interests of superpowers, and confronting external shocks and pressures. Adjacent to Russia, China, Iran, and Afghanistan, integrated CA states will be equipped with additional policy options due to its extremely important strategic location and geopolitical influence. Nowadays, the population of CA exceeds 60 million inhabitants. Abolishment of trade and tariff barriers will simplify labor mobility and free flow of capital. Since it represents vast markets, the region will be an extremely favorable environment for growth. Industries of consumer goods will have a boost. With influx of investments, textile and food industries, which are currently largely underdeveloped, will experience a continuous boom. Furthermore, these sectors also have considerable export potential, since, raw materials necessary for these industries are locally abundant. Over time, the abundance of cheaper labor resources will be a competitive advantage of CA industries compared to foreign producers. This might become the locomotive of integrated CA economy and will have profound effects, economic as well as social. The demographic profile of the CA area is unique with a high proportion of young people. Here, industrial development is crucial for eliminating the unemployment problem. Besides rich energy resources, the CA region also has plentiful ways to transport them, thanks to its strategic location: to China, to the sea (through Iran), to Turkey (through Caucasian states) and to Russia. This will make the region extremely important and powerful. The source of inter-ethnic conflicts is mainly rooted in social and economic hardships. Mostly, ethnic conflicts occur between indigenous populations and minorities. Sometimes, they are fueled by political reasons and inter-state disputes. Integration implies dissolution of such disputes. In fact, even historical evidence supports these ideas. During the Soviet period, all CA republics were part of single country. Back then, ethnic clashes were far less frequent than in the last 20 years. Between CA states, competition for the leadership in the region can be observed at present. This is a destabilizing factor, since outside powers frequently take advantage of such inter-state disagreements. Integration will prevent these trends and lead to one single powerful actor instead of several competing states. Some might argue that it is very unlikely for countries with different ethnic composition to integrate and actually the integration will intensify inter-ethnic tensions. But, there are examples of multi-ethnic states, such as Switzerland and Canada, which are quite successful and where various ethnic groups peacefully coexist and form single multi-ethnic society. One of the biggest fears among nations of CA is that they could lose their sovereignty through integration. They are afraid that one nation will dominate or even suppress the others. Nevertheless, the experience of European nations clearly demonstrated that such a situation can be avoided. Structure and system can be achieved if the principles of equality decision-making and benefits distribution are followed. The uniqueness of the European integration is characterized by the fact that smaller states are enabled to impose significant influence in decision-making and, subsequently, to enjoy significant benefits (Seidelmann 2004, p 3). Another good example would be the USA, where there is no "discrimination" among the states. The experience of European Union, which clearly demonstrated evident advantages of integration, might serve as an example and stimulus for the unification processes in the CA region in future.
Keywords: ddc:380